Kidney allograft subclinical rejection modulates systemic inflammation measured by C‐reactive protein at 1 year after transplantation. Issue 3 (30th January 2018) - García‐Carro, Clara; Dörje, Christina; Åsberg, Anders; Midtvedt, Karsten; Scott, Helge; Reinholt, Finn P.; Holdaas, Hallvard; Reisæter, Anna V.; Seron, Daniel
Abstract: Kidney allograft inflammation is associated with proinflammatory modifications of peripheral blood mononuclear cells, suggesting that renal inflammation contributes to systemic inflammation. Thus, the aim of this study was to evaluate the relationship between subclinical inflammation in surveillance biopsies performed at 1 year and systemic inflammation assessed by C‐reactive protein (CRP) levels at the time of biopsy. We analyzed 544 surveillance biopsies performed at 1 year that were classified as normal (n = 368), borderline (n = 148), or subclinical rejection (SCR) (n = 28). CRP levels were divided into quartiles. Patients in 1st, 2nd, and 3rd quartile were classified as low CRP (n = 408) and patients in the 4th quartile as high CRP (n = 136). Univariate analysis showed that the proportion of patients with SCR was higher in the high CRP group (10.3% vs 3.4%, P  = 0.0067). Multivariate analysis showed that independent predictors of high CRP were body mass index (odds ratio [OR] 1.072 and 95% confidence interval [CI] 1.027‐1.119), a positive urine culture at the day of the biopsy (OR 2.760 and 95% CI 1.205‐6.323), and the presence of SCR at 1‐year surveillance biopsy (OR 7.260 and 95% CI 3.530‐14.935). In summary, we describe that subclinical acute rejection constitutes an independent predictor of systemic inflammation as measured by CRP.